Influence of different plastic film packaging on the physiological and sensory quality of sweet oranges during cold and ambient storage - Alhassan, N; Abdulai, A; Mohammed , T (Journal of Postharvest Technology, 2022)
The effects of different plastic film packaging on physiological changes and sensory quality of sweet  oranges were evaluated during a 9-week storage at 4⁰C or ambient (20±2⁰C). The oranges were  seal-packaged with perforated polyphenylene films and biaxially-oriented polypropylene bags, and  another group was shrink-wrapped in films, while another group served as the control. Oranges  packaged with BOPP bags had the lowest weight loss at both cold storage (4⁰C) and ambient  (20±2⁰C) compared to the other packaged and control fruits. However, the TA declined with an  increase in TSS. Fruit sealed and packaged in plastic films preserved fruit firmness, taste, and flavor  compared to the control fruit. However, the highest firmness (29.5N), taste score (9.0), and flavor  acceptance (8.0) were observed with fruit sealed with BOPP bags at the end of storage. BOPP films  greatly reduced fruit decay to 5%, relative to the control with 25% decay. However, the treatments  should be evaluated for a wide range of citrus.
Keywords: Ambient temperature; cold storage; plastic films; sensory quality; sweet oranges; packaging